2015
DOI: 10.1021/ie503867p
|View full text |Cite
|
Sign up to set email alerts
|

Silica Aerogel Microparticles from Rice Husk Ash for Drug Delivery

Abstract: The present work describes an improved process for preparation of silica aerogel microparticles (SAMs) for drug delivery from rice husk ash (RHA), an inexpensive source rich in biocompatible silica. The wet gel microparticles were produced by a sol−gel method using water-in-oil emulsion, where a mineral oil replaced vegetable oil for easy separation using less energy. Taguchi design of experiments was used to optimize the parameters controlling the sol−gel method. The wet gel particles were dried with supercri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…The release profile of drugs loaded in silica aerogel is generally characterized by an immediate release of the drug due to the quick collapse and disintegration of the silica aerogel once in contact with aqueous solutions [18,171,201,206,207]. In general, the release rate of drugs with low water solubility is significantly increased when incorporated into silica aerogels if compared with the dissolution profile of the raw crystalline drug.…”
Section: Aerogel For Drug Deliverymentioning
confidence: 99%
“…The release profile of drugs loaded in silica aerogel is generally characterized by an immediate release of the drug due to the quick collapse and disintegration of the silica aerogel once in contact with aqueous solutions [18,171,201,206,207]. In general, the release rate of drugs with low water solubility is significantly increased when incorporated into silica aerogels if compared with the dissolution profile of the raw crystalline drug.…”
Section: Aerogel For Drug Deliverymentioning
confidence: 99%
“…3.6 Silica aerogel SA is a synthetic nano-porous, ultra-light, structure-controllable, solid material, which possesses excellent characteristics such as super-low bulk density (0.03-0.5 g/ cm 3 ), huge porosity (80-99%), a high specific surface area (500-1500 m 2 /g), low thermal conductivity, catalysis and a low dielectric constant [116][117][118]. It has a wide range of technological applications, therefore such as in insulation materials for buildings, membranes, pollutant absorbents, microelectronics, catalytic supports, drug carriers and dielectric materials [119,120].…”
Section: Silicon Nitridementioning
confidence: 99%
“…Furthermore, both rMBG and rMBG‐FA have no cytotoxicity in normal cells and showed excellent biocompatibility. Rajanna et al 260. reported that high loading and fast‐release kinetics of ibuprofen and eugenol which confirmed silica aerogel microparticles (SAMs) is suitable for drug delivery.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%
“…It has been found that RSAMs have a mesoporous structure with a surface area 274 m 2 g −1 , total pore volume 0.67 cm 3 g −1 , and an average pore diameter of 8.6 nm. This surface area is about 60% less, and the pore volume is 80% less, than that of SAMs 260. Industrial wastes from burnt RH could also become a cheap source of mesoporous silica for applications in the pharmaceutical industry.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%